(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
H2 is an ideal, clean and potentially sustainable energy carrier for the future due to its large energy content per weight, abundance and non-polluting nature. The selection of optimal H2 production technology depends on the H2-producing enzymes available. Thiocapsa roseopersicina contains a nitrogenase and several [NiFe] hydrogenases, which participate in H2 metabolism. In the present study, H2 production by the Hox1 soluble hydrogenase and the nitrogenase were investigated. The amount of H2 evolved by the nitrogenase enzyme was much higher than the amount produced by the Hox1 hydrogenase enzyme. By comparing the H2 production by nitrogenase from five short-chain organic acids (acetate, citrate, pyruvate, succinate, formate) the highest productivity of H2 ( 3 times) was observed in the presence of 4 g/l pyruvate. In this case, the pyruvate consumption was 100%, the biomass growth was equal to that of the control, therefore the produced H2 derived from pyruvate.